A sustainable approach to separate and recover indium and tin from spent indium–tin oxide targets. Issue 82 (13th November 2017) - Gu, Shuai; Fu, Bitian; Dodbiba, Gjergj; Fujita, Toyohisa; Fang, Baizeng
Abstract : A sustainable process is developed to recover indium and tin from spent ITO targets with high recovery rate and purity. Abstract : This study proposed an innovative method to separate and recover indium and tin from spent indium–tin-oxide (ITO) targets. ITO was first dissolved using concentrated HCl and then the leaching solution was distilled to recycle HCl and crystallize indium and tin ions. Next, the obtained crystals were transferred into SOCl2 solution under refluxing to remove the crystal water. By simply fractionating the mixture, anhydrous indium chloride, tin tetrachloride, and SOCl2 can be separated in a single operation. The recovery rate of InCl3 was ca. 99.6% with a purity of ca. 99.8%, while ca. 98.0% of SnCl4 was recovered with a purity of ca. 99.7%. Both the recovery rates and purities are the highest reported so far. Since all the reagents used in this process were carefully designed, almost all of the reagents can be reused. This is an environmentally friendly, economical and practical method to efficiently recycle ITO targets.